THE TRANSFORMATIONS IN THE CULTURE OF READING AMONG LITHUANIAN JEWS IN THE 2ND HALF OF THE 19TH C. – 1ST HALF OF THE 20TH C. - Lempertienė, Lara (Knygotyra, 2016)
The article is dealing with the changes in the culture of reading within the Jewish community of Vilnius and Lithuania during the second half of the 19th and the first half of the 20th century. It analyzes the transformation of the readers’ audience with regard to gender and age, the supply of reading materials and the means of their distribution. There were several periods of critical importance for those changes: the third decade of the 19th century when Lithuania became a center of Jewish Enlightenment – Haskalah movement in Russian Empire, and the inter-war period when the community underwent yet more radical modernization. The article presents the processes and the phenomena of the transformation and concludes with a notion of the extreme versatility in readers’ tastes and needs, as well as in the means of satisfying them, that the community reached on the eve of its annihilation during the Nazi occupation.
Keywords: Lithuanian Jews; reading; Jewish libraries